Straw strip mulching boosts potato yields by enhancing soil moisture and water use efficiency - Chen, Qian; Chang, Lei; Han, Fanxiang; Khan, Khuram Shehzad; Chai, Yuwei; Chai, Shouxi; Wang, Linlin; Ma, Jiantao (Frontiers in Plant Science, 2025)
IntroductionWater scarcity is a critical constraint limiting potato production in semi-arid rainfed areas. Mulching practices are recognized as effective water conservation strategies; Here, we investigated the effects of mulching practices on soil moisture and their impact on potato yield.MethodsA two-year field experiment (2018 – 2019) was conducted with five treatments, traditional bare-land planting without mulching (CK); large ridges and small furrows with only ridges mulched with black plastic film in fall (FPM); a partial-field mulching using whole cornstalks in straw mulching strips that alternate with planting strips without mulch in fall (FSM); large ridges and small furrows with only ridges mulched with black plastic film in spring (SPM); a partial-field mulching using whole cornstalks in straw mulching strips that alternate with planting strips without mulch in spring (SSM). We measured soil water storage (0–200 cm), yield, water-use efficiency (WUE), and stage-specific water consumption (WC).ResultsStudy results demonstrated that SSM and SPM significantly increased soil water storage (0–200 cm) by 6.7% and 8.4%, yield by 14.7% and 25.1%, and water-use efficiency (WUE) by 9.2% and 14.3%, respectively, compared to CK. Compared to spring mulching, the fall mulching outperformed in improving soil water retention and yield, increasing soil water storage by an average of 10.2% vs. 4.9%, and fresh potato yield by 17.8% vs. 11.8%. SSM and SPM reduced water consumption (WC) during the early growth stage (planting-to-budding) by 8.2–9.8%, conserving water for later use. This conserved water was then available during the critical yield-forming period, leading to increased WC during budding-to-tuber expansion by 10.3–11.3%. SSM increased WC more than FSM (12.3% vs. 10.2%), while FPM increased WC more than SPM (20.3% vs. 13.1%).DiscussionThe findings indicated that both the straw strip mulching (SM) and plastic film mulching (PM) optimized the water consumption structure. Fall mulching generally outperformed spring mulching because it captured and conserved autumn and winter precipitation more effectively, resulting in higher soil water storage at planting. Both straw and plastic film mulching improve water use and potato yields, with fall application were most effective. However, for sustainable production, straw strip mulching is recommended, as it offers both high crop yields and significant environmental benefits.